A CASE STUDY ON INTEGRATED LOGISTICS BERHAD - Johar,; MGM,; Yajid, Mohd Shukri Ab; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The mainly important tool to generate alternative strategies would be TOWS Matrix. Prior to that, the SEPT analysis and SWOT analysis had been done to enable the matching process in the TOWS Matrix to be accomplished. There are other related models and tools to support the analysis. With the assistance of ILB administrations the client had the option to diminish its request process duration to its clients while decreasing stock- outs and by and large appropriation costs, as reserve funds in transportation was a lot more worthy than the additional completely troubles expenses of the new stockroom office. ILB business advancement distinguished a few appropriate open distribution center organizations and arranged to support the administrations from these organizations. The groupings were finished, giving the beneficiaries the entirety of the data they expected to assess their capacity to offer the necessary types of assistance and to build up serious valuing for those administrations. Following choice of the best distribution center decision, ILB arranged a usage plan intended to dispatch the administrations of the chose supplier in convenient and proficient way. To really sweeten the deal, and most likely as the consequence of having a stock near the market, deals expanded by 17% more than foreseen over the resulting two years. ILB’s client was satisfied with results.